DIFFERENT IRRIGATION SYSTEMS AFFECT THE YIELD AND WATER USE EFFICIENCYOF KINNOW MANDARIN (CITRUS RETICULATA BLANCO.) - A. Raza1; M. A. Zaka; T. Khurshid; M. A. Nawaz; W. Ahmed; M. B. S. Afzal (Journal of Animal and Plant Sciences, 2020)
Considering the scarce water resources, low average yield of citrus fruits, and haphazard irrigation system adopted in Pakistan; a study was conducted on 25 year old Kinnow mandarin plants grafted onto Rough lemon (Citrus jambhiri Lush.) during 2011–2015. In this study four modes of irrigation that includes drip irrigation (DI), full cover sprinkler (FCS), strip cover sprinkler (SCS) and traditional flood irrigation (TFI) were used. The yield, quality and water use efficiency (WUE) were evaluated. This study was conducted at Citrus Research Institute (CRI), Sargodha, Pakistan. To monitor the moisture level in the soil, tensiometers were installed in each block at the depth of 30, 60 and 90 cm in the root zone. A flume meter was used to measure the total quantity of water applied under flood irrigation system. The Kinnow plants growing under TFI system produced a fruit yield of 26.12 t ha-1 (687 fruits tree-1 and 104.55 kgtree-1) and WUE was only 2.29 kg m-3, however 40.46% higher yield (1288 fruitstree-1 and 181kgtree-1) was obtained from plants grown under DI system compared with TFI and WUE was 4.85 kgm-3. The 55% water saving was attained using DI compared with TFI. Similarly, significantly higher yield of 28.45% (1029 fruit tree-1 and 151kgtree-1) and 27.19% (1045 fruit tree-1 and 147.92 kgtree-1was obtained by using FCS and SCS, respectively compared with TFI, and WUE in FCS and SCS system was 3.03 kg m-3and 3.35 kg m-3, respectively as compared with TFI (2.29 kg m-3). It is concluded that DI is superior in terms of higher yield and WUE therefore for Kinnow growers DI is recommended to get higher yield and enhance the WUE.
Keywords: citrus; irrigation methods; high efficiency irrigation systems; yield; fruit quality